High intensity interval training in patients with COPD: A bibliographic review - Lima, Rubens A.; Ferreira, Fátima S.; de França, Natália B. M.; Ferreira, Juiana R.; Sales, Késsia N. A. (Brazilian Journal of Health and Biomedical Sciences, 2019)
Introduction: Chronic obstructive pulmonary disease (COPD) is characterized by chronic limitation of airflow associated with a variety of pathological pulmonary changes. Pulmonary rehabilitation programs seek to improve several aspects of patients with COPD. Regarding the use of physical conditioning in approaches to COPD, High Intensity Interval Training (HIIT) is defined by high intensity interval sessions with rest sessions. Objective: To evaluate the effectiveness of HIIT in patients with COPD. Materials and methods: A narrative review of the literature was made through the Virtual Health Library databases (LILACS, MEDLINE) and PEDro, using the descriptors High Intensity Interval Training, Chronic Obstructive Pulmonary Disease and Rehabilitation, in order to obtain a synthesis on the insertion of HIIT in the pulmonary rehabilitation of patients with COPD. Articles that addressed HIIT in individuals with COPD were included and those that did not correspond to the topic were excluded. Conclusion: In spite of the need for further studies on this topic, HIIT can be used in the pulmonary rehabilitation of patients with COPD with moderate to severe airflow limitation. Keywords: Chronic obstructive pulmonary disease; High intensity interval training; Pulmonary rehabilitation.